Purification, crystallization and preliminary characterization of a putative LmbE-like deacetylase from Bacillus cereus - Fadouloglou, Vasiliki E. (International Union of Crystallography, 2006)

(untitled)
The Bacillus cereus BC1534 protein, a putative deacetylase from the LmbE family, has been purified to homogeneity and crystallized using the hanging-drop vapour-diffusion method. Crystals of the 26 kDa protein grown from MPD and acetate buffer belong to space group R32, with unit-cell parameters a = b = 76.7, c = 410.5 Å (in the hexagonal setting). A complete native data set was collected to a resolution of 2.5 Å from a single cryoprotected crystal using synchrotron radiation. As BC1534 shows significant sequence homology with an LmbE-like protein of known structure from Thermus thermophilus, molecular replacement will be used for crystal structure determination.